Concursos de arquitetura como alternativa para a preservação do patrimônio histórico construído - Vescia, Jenifer Petry (2022)
Historically, achievement competitions for the selection of architectural projects have been a common practice. Whether by opportunity or recognition, countless architects participate in these competitions and great names in architecture have gained notoriety through them. This research, linked to the Postgraduate Program in Cultural Heritage, in the research theme Architecture and Material Heritage, aims to analyze the efficiency and the possibilities of architectural competitions in historic building’s interventions, whether they are or not subject to legal protection. The issue of heritage preservation is a social and diverse practice, reproducing the contradictions of the society and their conflicts. The confrontation between public policies, preservation and private interests manifests controversies that demand new practices in heritage preservation. In Brazil, although significant competitions have highlighted practices and encouraged national architecture, the method in the country still requires consistency and regulation. Several mistakes in the realization of architectural competitions reflect on limited practical results, with only a few winners being hired and works being built. With the bibliographical and exploratory method, through a bibliographical referential that goes through the history and scope of architectural competitions, as well as an analysis of the legislation, this work converges to competition’s case studies, selected from this research. The results seem to show that, although there are means of legal protection, there is resistance by contractors and public managers to hold competitions, a factor that reflects in the low attendance of this type of competition in Rio Grande do Sul. In general, the bureaucratic barriers and lack of confidence in the process and its results bring low expectations for the realization of architectural competitions in historical heritage. Through these analyses and comparisons, a guiding booklet was produced for the organization of architectural competitions in heritage sites, which brings together characteristics, regulations and comments for the implementation of these competitions in an effective and efficient manner in the State of Rio Grande do Sul.